Relación del estado nutricional con anemia ferropenica en niños 3 a 5 años de la comunidad los Sauces, octubre 2018-abril 2019 - Bacuilima Sanchez, Rosa Stefania (2019)
The present work was carried out in order to verify if there is a relationship between the nutritional status and iron deficiency anemia, of children from 3 to 5 years of age in the community of Los Sauces, for which we have observed that many of the mothers of family or caretakers of children, pay little attention to the nutritional status of their children today. For this reason this research was conducted to allow the authors to assess the nutritional status, through anthropometric indicators and their relationship with the degree of anemia, to children aged 3 to 5 years of the Community of Los Sauces. In order to assess the nutritional status of children, the Oms Growth Curves have been used as a reference, in order to make the graph in the appropriate table. Once the children were assessed, it was found that there is a prevalence of low weight and normal height. Despite the child being in an adequate nutritional status, he has mild or moderate anemia. Then we proceeded to store and classify the data in the Database, the same one that we used to obtain the tabulations of the results with the help of the Chi-square. Reason for which a proposal of nutritional educative plan was proposed, to train the mothers of family and thus, to contribute to diminish the prevalence of malnutrition and ferropenic anemia.